Pengaruh Kepemimpinan, Pelatihan, dan Motivasi Kerja Terhadap Kapabilitas Karyawan di Perusahaan Perkebunan PT. XYZ (Indo-MathEdu Intellectuals Journal, 2025)
This research examines the influence of leadership, training, and work motivation on employee capabilities at PT. XYZ, a palm oil plantation company post-acquisition, to address the suboptimal employee capabilities. This study uses an explanatory quantitative approach, collecting data from a sample of 100 permanent employees of PT. XYZ in several provinces in Indonesia. Data was obtained through a validated Likert scale questionnaire that was tested for reliability, then analyzed using SPSS for descriptive statistics, classical assumption tests, and multiple regression analysis. The results of the analysis indicate that individually, leadership and work motivation have a positive and significant impact on employee capabilities. However, training shows a significant negative impact that is unexpected, possibly due to a lack of relevance or ineffectiveness. Importantly, the combined influence of leadership, training, and work motivation simultaneously has a significant positive impact on employee capabilities, explaining 43.5% of the variance. This study concludes that, although leadership and motivation are positive and training shows a negative individual effect, the synergistic impact of these three factors significantly enhances employee capabilities at PT. XYZ, underscoring the importance of integrated human resource strategies in a dynamic organizational environment.